Immediate Effects of Nasalance Exercises on Patients with Organic Dysphonia - Kuranova, Liudmila; Kainz, Marie Anne; Echternach, Matthias; Döllinger, Michael; Köberlein, Marie (Journal of Otolaryngology-Head & Neck Surgery, 2025)
ImportanceNasalance exercises (also known as resonance exercises) are widely used in voice therapy. Understanding their effects can guide therapeutic approaches and surgical decisions.ObjectiveTo analyze the immediate effects of nasalance exercises on vocal fold oscillation in patients with vocal fold mass lesions and a recommendation for phonosurgery.DesignProspective observational study following the STROBE guidelines.SettingDepartment of Phoniatrics, university hospital.ParticipantsSeven patients with vocal fold mass lesions (6 with polyps, 1 with Reinke edema) and indication for surgery.Intervention/ExposuresParticipants performed nasalance exercises for 10 minutes. Recordings were taken before the exercise (pre), immediately after (post0), and 10 minutes after completion (post10). Subjects phonated vowel [i:] on a sustained pitch (250 Hz for females, 125 Hz for males) at a comfortable level of loudness.Main Outcome MeasuresData were collected using transnasal high-speed videoendoscopy, a Rothenberg mask for airflow measurement, electroglottography, and audio recordings. Extracted parameters were: nasalance, open quotient (OQ), closing quotient (ClQ), sound pressure level (SPL), Jitter, and cepstral peak prominence (CPP).ResultsNasalance increased immediately after the exercises for 6 out of 7 subjects. OQ values varied: they increased in 3 subjects, decreased in 3, and remained unchanged in 1. No consistent relationship was found between SPL and ClQ. Jitter increased in 5 subjects. CPP did not show clear tendencies. The effects on voice parameters did not persist 10 minutes postexercise. There were no significant correlations with age, sex, or preintervention voice indices (Voice Handicap Index, Dysphonia Severity Index).ConclusionsIn patients with organic dysphonia and an indication for surgery, a raised nasalance value directly after the execution of nasalance exercises does not necessarily lead to stabilized voice parameters, and the possible effects do not seem to be persistent.RelevanceNasalance exercises might not provide sustained benefits in stabilizing vocal fold vibrations in subjects with an indication for surgery.
CRIS-Team Scopus Importer:2025-06-06
Keywords: high-speed videoendoscopy; nasalance exercises; organic dysphonia; resonant voice; vocal fold mass lesion; voice therapy